HUBUNGAN PERILAKU CARING DENGAN KEMAMPUAN PERAWAT DALAM MELAKSANAKAN KESELAMATAN PASIEN DI IGD RSU GMIM PANCARAN KASIH MANADO - Rahmat Hidayat Djalil; Helly Katuuk (Universitas Muhammadiyah Manado, 2020)
The application of the patient safety system in various hospitals has aspects that must be improved, including the ability and attitude of health service executing officers. Nurses who are competent in patient safety are judged by their behavior when providing nursing care. Attitude or behavior is a nurse's readiness to take an action from experience that is given a dynamic influence on patient response, nurses are influenced by the quality of clinical and non-clinical skills related to the ability to provide nursing care. The purpose of this study was to determine whether there is a relationship between caring behavior and the ability of nurses to carry out patient safety. This research is a quantitative research design with analytical descriptive method. Samples were taken based on the number of respondents who met the criteria and in accordance with the statistical test requirements as many as 32 respondents using total sampling. The data was collected by distributing questionnaires to each respondent. Furthermore, the data that has been collected is processed using the SPSS version 16.0 computer program to be analyzed by using the Chi-Square statistical test with a significance level of (a) 0.05. The results in this study that there is a relationship between caring behavior and the ability of nurses to carry out patient safety at GMIM Pancaran Kasih Hospital Manado p = 0.000, this p value is smaller than the value of a = 0.05. The conclusion in this study is that there is a relationship between caring behavior and the ability of nurses to carry out patient safety at RSU GMIM Pancaran Kasih Manado. Suggestions are expected to take advantage of the results that have been obtained by applying them in health services.